2007
DOI: 10.1007/s10554-007-9289-6
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole stress echocardiography stratifies outcomes of asymptomatic patients with recent myocardial revascularization

Abstract: DipSE yields appropriate risk stratification and provides incremental prognostic value over clinical variables even in asymptomatic patients with prior complete myocardial revascularization. A negative DipSE portends a benign prognosis (<5% event rate/year) in such population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
1
0
6
Order By: Relevance
“…In particular, the evidence of ischemia at SE adds significant prognostic information to that provided by clinical data and resting echo. This reinforces previous observations with exercise [10], dobutamine [11], and dipyridamole [12] SE. Arruda et al [10] reported echocardiographically assessed exercise ejection fraction and diabetes mellitus as independent predictors of outcome in 718 patients undergoing CABG 5.7 ± 4.7 years before the index SE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, the evidence of ischemia at SE adds significant prognostic information to that provided by clinical data and resting echo. This reinforces previous observations with exercise [10], dobutamine [11], and dipyridamole [12] SE. Arruda et al [10] reported echocardiographically assessed exercise ejection fraction and diabetes mellitus as independent predictors of outcome in 718 patients undergoing CABG 5.7 ± 4.7 years before the index SE.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, also this study dealt with a population at increased risk of unfavourable outcome. More recently, Rossi et al [12] investigated the prognostic value of dipyridamole SE in 104 symptom-free patients with recent (b 12 months) complete revascularization either by CABG or percutaneous coronary intervention. In this low-risk population, ischemia at SE was a multivariable predictor of the composite endpoint of cardiac death and nonfatal acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Nos oito pacientes submetidos ao protocolo com dipiridamol-dobutamina não se observou sinais ou sintomas durante a realização do exame. Alguns protocolos podem desencadear maior sintomatologia como é o caso do dipiridamol (1,4,5) , o qual pode ocasionar graus variados de cefaléia, calor e rubor facial, cansaço, ardência no sítio de punção venosa e a possibilidade de dor precordial e/ou angina típica. Estes dados foram corroborados por este estudo, principalmente, no uso do dipiridamol UF, quando comparado com os outros dois testes estudados.…”
Section: Metodologiaunclassified
“…A ocorrência de cefaléia (5) , no uso do dipiridamol, é atribuída a sua ação vasodilatadora. Todavia, conforme o idealizador do eco-stress (10,11) , somente em 2% dos casos, a queixa de cefaléia impede a continuação do exame.…”
Section: Sinais E Sintomasunclassified
See 1 more Smart Citation